Józef Tischner’s Thinking According or Against Values? - Stachewicz, Krzysztof (Filozofia Chrześcijańska, 2011)
The article reconstructs a certain element of the evolution in Józef Tischner’s thinking. Initially representing orthodox phenomenology, Tischner situated his philosophy in exiological paradigm seeing in values the most fundamental reality and the main object of philosophical research. Later, thanks to agathological dimensions he put aside the language of values and sometimes doubted adequacy of values as philosophical category. Tischner revealed courage when he was able to radically revise his former views according to the principle: amicus Plato, magis tamen amica veritas.